Kepemimpinan Wanita Dalam Perspektif Hadis Nabi SAW (Pemahaman Makna Tekstual dan Kontekstual) - Tangngareng, Tasmin (Sulesana: Jurnal Wawasan Keislaman, 2017)
Women leadership is never-ending issue to discuss. Some Islamic theological considerations always become the main reasons to position its main teaching, supports equality between men and women. This article tries to present textual and contextual analyzes around women leadership in public affairs. It is textually found that prophetic traditions and opinions of most Muslim scholars badly state that women leadership in public affairs is prohibited but contextually it is not. It seems that in reasoning the issues of women leadership. Contextual anderstanding must be firstly considered.